Protocol to study ductal progenitor-like cells from the adult human pancreas using 3D suspension and methylcellulose-based culture systems - Heather N. Zook; Janine C. Quijano; Jose A. Ortiz; Cecile Donohue; Neslihan Erdem; Hsun Teresa Ku (STAR Protocols)
Summary: Primary human ductal progenitor-like cells derived from donated pancreas have the potential to serve as a source of therapeutic insulin-producing beta cells for the treatment of diabetes. Here, we present a protocol for studying ductal progenitor-like cells using a good manufacturing practice (GMP)-compatible 3D suspension culture system and a methylcellulose- and Matrigel-based 3D colony assay. We describe steps for dispersing and cryopreserving human pancreatic cells and initiating and maintaining cultures. We then detail how to prepare ductal spheroids or colonies for downstream applications.For complete details on the use and execution of this protocol, please refer to Zook et al.1 and Quijano et al.2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.